Novel Optimization Technique for PI Controller Parameters of ac/dc PWM Converter using Genetic Algorithms - Vishnu Mohan Mishra; Amar Nath Tiwari; Nikhlesh Kumar Sharma (International Journal of Power Electronics and Drive Systems (IJPEDS), 2012)
The aim of this paper is to present a novel control scheme and designing of reactance parameter of PWM convereterand,  find the optimized value of parameters for voltage PI controller for three phase ac/dc PWM converter. Using new trends Genetic algorithms- are discussed, as well.Paper describes the application of Genetic Algorithms for optimization of controller parameters of PWM converter. The behavior of the stability region is plotted with different sampling periods.Genetic Algorithms used for off-line searching Using the MATLAB, the simulation model of the dc- link PWM ac/dc converter is built up. According to the simulation results, it is known that, the presented control strategy is feasible and valid, and the converter can work well under dc motor load condition, and thus the total harmonics distortion (THD) can be reduced quickly and effectively. The PWM rectifier operates as a rectifier to supply dc power to its load a dc motor and at the same time, to improve the power factor and to compensate harmonics drawn from non-linear loads connected on the ac line.DOI: http://dx.doi.org/10.11591/ijpeds.v2i2.156